A promising role of Insecticide Treated Bed-Nets (ITNs) against Malaria: A way forward. - Banda, Jane; Hamat, Rukman Awang; Osman, Malina (International Institute for Science, Technology and Education, 2012)
Malaria is both preventable and treatable yet the disease has continued to cause high death tolls annually. This picture is eminent in low income countries of the world where the disease is endemic although close to half of the world’s population is at risk. To date, malaria is still one of the most serious global health threats, exerting grave misery upon mankind. Africa is worst hit. The surest tool with proven potential of yielding low transmission rates of close to zero from very high is vector control. The protective benefits of vector control are principally protecting people from infective mosquito bites. Insecticide-treated bed nets (ITNs) are the most widely used vector control tool used since World War II. In the recent past, treated bed nets have been widely scaled-up. Despite the obvious proven benefits, the initiatives have not been without challenges; the community which is the major stake-holder seems left out in this battle of more than a century.